Social interaction and sickness absence - Assar Lindbeck; Mårten Palme; Mats Persson (Center for Economic Studies and ifo Institute (CESifo), 2008)
Does the average level of sickness absence in a neighborhood affect individual sickness absence through social interaction on the neighborhood level? To answer this question, we consider evidence of local benefit-dependency cultures. Well-known methodological problems in this type of analysis include avoiding the so-called reflection problem and disentangling the causal effects of group behavior on individual behavior from the effects of individual sorting on neighborhoods. Based on data from Sweden, we adopt several different approaches to deal with these problems. The results are robust in the sense that regardless of approach and identifying assumptions, we obtain statistically significant estimates indicating group effects.
Keywords: H56; I38; J22; Z13; 330; sick-pay insurance; work absence; moral hazard; social norms; Krankheit; Fehlzeit; Gesetzliche Krankenversicherung; Erwerbsunfähigkeitsrente; Moral Hazard; Soziale Beziehungen; Soziale Norm; Schätzung; Schweden